Signal Filtering Enabled by Spike Voltage‐Dependent Plasticity in Metalloporphyrin‐Based Memristors. Issue 43 (12th September 2021) - Wang, Zhiyong; Wang, Laiyuan; Wu, Yiming; Bian, Linyi; Nagai, Masaru; Jv, Ruolin; Xie, Linghai; Ling, Haifeng; Li, Qi; Bian, Hongyu; Yi, Mingdong; Shi, Naien; et al.
Abstract: Neural systems can selectively filter and memorize spatiotemporal information, thus enabling high‐efficient information processing. Emulating such an exquisite biological process in electronic devices is of fundamental importance for developing neuromorphic architectures with efficient in situ edge/parallel computing, and probabilistic inference. Here a novel multifunctional memristor is proposed and demonstrated based on metalloporphyrin/oxide hybrid heterojunction, in which the metalloporphyrin layer allows for dual electronic/ionic transport. Benefiting from the coordination‐assisted ionic diffusion, the device exhibits smooth, gradual conductive transitions. It is shown that the memristive characteristics of this hybrid system can be modulated by altering the metal center for desired metal–oxygen bonding energy and oxygen ions migration dynamics. The spike voltage‐dependent plasticity stemming from the local/extended movement of oxygen ions under low/high voltage is identified, which permits potentiation and depression under unipolar different positive voltages. As a proof‐of‐concept demonstration, memristive arrays are further built to emulate the signal filtering function of the biological visual system. This work demonstrates the ionic intelligence feature of metalloporphyrin and paves the way for implementing efficient neural‐signal analysis in neuromorphic hardware. Abstract : A novel memristor based on a metalloporphyrin/oxide hybrid heterojunction is developed, in which the metalloporphyrin‐based intelligent semiconductors allow for dual electronic/ionic transport. The memristive devices exhibit unipolar plasticity, which can qualify the signal filtering function of the human visual system by programming different positive voltage spikes at fixed frequencies and time intervals.